Pengembangan Sistem Penyewaan Lapangan Olahraga Komersil Berbasis Website dengan Metode Agile pada Gedung Olah Raga ( GOR ) Dimyati di Kota Tangerang - Mahdiaroji; M.Fikri Hidayat; Dzaki Rozaan; Daffa Fauziran; Aries Saifudin (Journal of Research and Publication Innovation, 2023)
This research has problems with time and distance in the process of leasing commercial sports fields at the Dimyati Sports Hall (GOR), Tangerang City. This problem arises because potential customers must physically come to the GOR location to place an order for a sports field, which can take time and hinder efficiency. To solve this problem, this research proposes the development of a website-based commercial sports field rental system using the Agile method. The Agile method was chosen for its flexibility in responding to changes and meeting customer needs quickly. In applying the Agile method, the development of the sports field rental system is carried out iteratively, involving prospective customers and GOR-related parties in the development process. The development team communicates continuously with customers to understand their needs and make system adjustments in real-time. This approach enables the development of more adaptive, relevant and high-quality systems. The results of applying the Agile method to the problem of leasing sports fields at Dimyati Sports Hall show several significant benefits. First, a website-based sports field rental system allows potential customers to place orders easily and quickly through an online platform, reducing time and distance limitations. Second, field availability and match schedules can be easily accessed through the website, making it easier for prospective customers to plan their sports activities. Third, customer involvement in the development process ensures that the system accurately meets their requirements.